Acute Femoral Occlusion After Adjunctive Angio-Seal Usage in Vascular Closure Following Transcatheter Aortic Valve Replacement - Liu, Sheng-Fu (JACC Case Rep, 2019)
We report 3 patients with acute femoral occlusion after adjunctive Angio-Seal use during transfemoral transcatheter aortic valve replacement. All occlusions were recanalized by applying elaborative strategies for chronic total occlusion recanalization. Our experience reminds operators to cautiously use the Angio-Seal as a bailout treatment, especially in patients with high-risk clinical features. (Level of Difficulty: Intermediate.)